2017
DOI: 10.1177/0146167217741313
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Stigma on Health and Well-Being: A Taxonomy of Concealment, Course, Disruptiveness, Aesthetics, Origin, and Peril Across 93 Stigmas

Abstract: Most individuals are stigmatized at some point. However, research often examines stigmas separately, thus underestimating the overall impact of stigma and precluding comparisons across stigmatized identities and conditions. In their classic text, Social Stigma: The Psychology of Marked Relationships, Edward Jones and colleagues laid the groundwork for unifying the study of different stigmas by considering the shared dimensional features of stigmas: aesthetics, concealability, course, disruptiveness, origin, pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
209
1
12

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 196 publications
(224 citation statements)
references
References 99 publications
2
209
1
12
Order By: Relevance
“…In the future, we can also generate more sophisticated hypotheses by fitting conspiracy theories into known dimensions of stigma (Pachankis et al., ). A first relevant dimension of stigma is its concealability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the future, we can also generate more sophisticated hypotheses by fitting conspiracy theories into known dimensions of stigma (Pachankis et al., ). A first relevant dimension of stigma is its concealability.…”
Section: Discussionmentioning
confidence: 99%
“…According to Goffman (), a stigma is “an attribute that extensively discredits an individual” (p. 3). These attributes, such as skin color (Pinel, Warner, & Chua, ), sexual orientation (Lewis, Derlega, Griffin, & Krowinski, ), physical or mental disabilities (Crandall & Moriarty, ; Rüsch, Angermeyer, & Corrigan, ), or religious (non)belief (Gervais & Najle, ; Nugier et al., ; Pachankis et al., ) may be of various kinds, as a function of the social context (Major, ). A great deal of research has been devoted to the topic of stigma (Link & Phelan, ; Major & O'Brien, ), including the study of its nature (e.g., the different characteristics of stigma such as controllability, concealability, and dangerousness; Frable, ; Major, ; Quinn, ), its origins (Kurzban & Leary, ), and its social‐psychological consequences (Major & O'Brien, ).…”
Section: Social Stigma: Definition Psychological Consequences and Cmentioning
confidence: 99%
“…Decades of social science research have repeatedly and robustly shown that stigma is pervasive, that it affects a substantial number of people, that it is a source of social inequalities in life chances that are themselves powerful determinants of health (including, but not limited to, education and academic achievement, housing, employment and income, and beneficial social relationships), and that it has a direct, corrosive impact on the health of populations . For these reasons, stigma has been conceptualized as a fundamental cause of population health inequalities …”
Section: Stigma and Population Health Inequalitiesmentioning
confidence: 99%
“…The lack of existing protections is further emphasized when one considers that the work of Hatzenbuehler and colleagues, whose work we drew on to create Figure , underestimates the full influence of stigma on life chances, because they chose only six stigmatized statuses that had been the focus of quantitative (eg, meta‐analytic) and qualitative reviews. Although the field has not reached consensus on the exact number of stigmatized identities/statuses, recent work by Pachankis et al . identifies as many as 93 stigmatized categories experienced in the general population (eg, criminal record, drug dependency, Muslim, undocumented immigrant, homeless), the vast majority of which are not explicitly recognized in the legal system as protected classes.…”
Section: Limits Of Antidiscrimination Law: Conceptualmentioning
confidence: 99%
See 1 more Smart Citation